Inferno : (a poet's novel) - Myles, Eileen (OR Books, 2010)
From its beginning, poet, essayist and performer Eileen Myles' chronicle transmits an energy and vividness that will not soon leave its readers. Her story of a young female writer, discovering both her sexuality and her own creative drive in the meditative and raucous environment that was New York City in its punk and indie heyday, is engrossing, poignant, and funny. This is a voice from the underground that redefines the meaning of the word.